Synthesis of Zeolite NaA from Low Grade (High Impurities) Indonesian Natural Zeolite - Asalil Mustain; Gede Wibawa; Mukhammad Furoiddun Nais; Miftakhul Falah (Indonesian Journal of Chemistry, 2014)
The zeolite NaA has been successfully synthesized from the low grade natural zeolite with high impurities. The synthesis method was started by mixing natural zeolite powder with NH4Cl aqueous solution in the reactor as pretreatment. The use of pretreatment was to reduce the impurities contents in the zeolite. The process was followed by alkaline fusion hydrothermal treatment to modify the framework structure of natural zeolite and reduce the SiO2/Al2O3 ratio. Finally, the synthesized zeolite was calcined at 600 °C for 2 h. The final zeolite product was characterized by X-ray fluorescence (XRF), X-ray diffraction (XRD) and scanning electron microscopy (SEM). The results showed that the morphology of the zeolite NaA was cubic shape as observed by SEM analysis and the synthesized zeolite NaA with pretreatment gave less impurity than without pretreatment.